ELECTROMAGNETIC PIPE INSPECTION INVERSION WITH ADAPTIVE FILTER FOR ARTIFACT REMOVAL - Dai, Junwen; Hill, Freeman L; FOUDA, Ahmed E (2023)
Aspects of the subject technology relate to systems, methods, and computer-readable media for accounting for artifacts in pipe measurements made by an electromagnetic pipe inspection tool. Measurements gathered in a plurality of pipes across different depth points are accessed. Initial estimates of an attribute associated with the plurality of pipes are made for each pipe and a total estimate of the attribute for the plurality of pipes as a whole are made across the different depth points. Corresponding initial estimates of the attribute for each pipe are filtered to remove an artifact present in at least one of the corresponding initial estimates while the total estimate is preserved. Corresponding final estimates of the attribute for each pipe are determined based on both the measurements and corresponding filtered initial estimates of the attribute for each pipe. Integrity of each pipe can be determined based on the corresponding final estimates of the attribute.